Enhanced neuroinvasion by smaller, soluble prions - Cyrus Bett; Jessica Lawrence; Timothy D. Kurt; Christina Orru; Patricia Aguilar-Calvo; Anthony E. Kincaid; Witold K. Surewicz; Byron Caughey; Chengbiao Wu; Christina J. Sigurdson (Acta Neuropathologica Communications, 2017)
Abstract Infectious prion aggregates can propagate from extraneural sites into the brain with remarkable efficiency, likely transported via peripheral nerves. Yet not all prions spread into the brain, and the physical properties of a prion that is capable of transit within neurons remain unclear. We hypothesized that small, diffusible aggregates spread into the CNS via peripheral nerves. Here we used a structurally diverse panel of prion strains to analyze how the prion conformation impacts transit into the brain. Two prion strains form fibrils visible ultrastructurally in the brain in situ, whereas three strains form diffuse, subfibrillar prion deposits and no visible fibrils. The subfibrillar strains had significantly higher levels of soluble prion aggregates than the fibrillar strains. Primary neurons internalized both the subfibrillar and fibril-forming prion strains by macropinocytosis, and both strain types were transported from the axon terminal to the cell body in vitro. However in mice, only the predominantly soluble, subfibrillar prions, and not the fibrillar prions, were efficiently transported from the tongue to the brain. Sonicating a fibrillar prion strain increased the solubility and enabled prions to spread into the brain in mice, as evident by a 40% increase in the attack rate, indicating that an increase in smaller particles enhances prion neuroinvasion. Our data suggest that the small, highly soluble prion particles have a higher capacity for transport via nerves. These findings help explain how prions that predominantly assemble into subfibrillar states can more effectively traverse into and out of the CNS, and suggest that promoting fibril assembly may slow the neuron-to-neuron spread of protein aggregates.